Anti-aging effects of fenugreek cream on postmenopausal skin: A randomized controlled trial - Shannaz Nadia Yusharyahya, Kusmarinah Bramono, Wresti Indriatmi, Marcel Prasetyo, Purwantyastuti Ascobat, Andon Hestiantoro, Anak Agung Gde Putra Wiraguna (Journal of Applied Pharmaceutical Science, 2021)
Postmenopausal hypoestrogenism is associated with skin aging, for which phytoestrogen derived from the seeds of Trigonella foenum graecum (fenugreek) is expected to be an alternative solution to reduce wrinkles and increase the thickness of postmenopausal women’s skin. This study was a randomized, double-blind, controlled 12-weeks trial conducted at a general hospital in Jakarta, Indonesia, from January to November 2019. Subjects were 50 postmenopausal women divided into two groups: the intervention group was given 5% fenugreek cream and base cream was given to the placebo group. The results of the independent t-test showed that both groups were able to achieve statistically significant improvement in wrinkle scores on the forehead, crow’s feet, and nasolabial folds which was assessed by photography scoring based on Bazin’s skin aging atlas for Asian skin volume 2 but there was no significant disparity between both groups at all time points. Dermal thickness was assessed by high-resolution ultrasound GE LOGIQ E9 (18 MHz), which showed similar results for both groups with significant improvements in the 8th week compared to baseline and a significant decrease by the 12th week. No significant differences were observed in the skin wrinkle score and skin thickness after the application of fenugreek cream compared to placebo. We suspect that a concentration of 5% was not adequate for the expected antiskin aging effects. Further studies are necessary to determine a more appropriate fenugreek concentration to permit clinical use as an antiskin aging therapy in postmenopausal women.
Keywords: Dermal thickness, fenugreek, postmenopausal skin, skin wrinkle.